2022
DOI: 10.3390/su14148861
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Ascorbic Acid and Alpha-Tocopherol on Chickpea (Cicer arietinum L.) Grown in Water Deficit Regimes for Sustainable Production

Abstract: Drought is a major abiotic stress forced by the changing climate that affects plant production and soil structure and functions. A study was conducted to explore the impacts of ascorbic acid (AsA) and α-tocopherol (α-toc) on the agro-physiological attributes and antioxidant enzymes of chickpea grown in water deficit regions. The results of the soil analysis showed that the electrical conductivity (EC) and pH were decreased from 521 mS/m and 7.08 to 151 mS/m and 6.6 in 20-day drought regimes, respectively. Agro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Our findings are in agreement with other results [ 91 , 92 , 93 ] which reported that the simultaneous increase in the activity of these antioxidant enzymes contributes to an increase in the application of brown seaweed liquid fertilizer. Similar observations were observed in the onion plant when treated with the foliar application of exogenous antioxidant compounds [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. The author found an increase in POX activity when the plant was treated by alpha tocopherol.…”
Section: Resultssupporting
confidence: 79%
“…Our findings are in agreement with other results [ 91 , 92 , 93 ] which reported that the simultaneous increase in the activity of these antioxidant enzymes contributes to an increase in the application of brown seaweed liquid fertilizer. Similar observations were observed in the onion plant when treated with the foliar application of exogenous antioxidant compounds [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. The author found an increase in POX activity when the plant was treated by alpha tocopherol.…”
Section: Resultssupporting
confidence: 79%
“…However, there have been different outcomes of protein accumulation in plants under stress conditions, and the increased expression of these proteins contributes to plant stress management. 42 In this study, a decrease in the protein concentration was recorded in plants subjected to drought stress. Increasing the total protein content as osmotic defenders is critical for plant osmoregulation under water stress circumstances.…”
Section: ■ Discussionmentioning
confidence: 86%
“…This condition is critical for other legumes, such as the chickpea plant, as it results in less N for protein biosynthesis and decreased grain output. , Previous studies showed that some proteins increased during abiotic stress conditions such as drought, salinity, heat, and cold. This indicates that protein is essential in the plant response to drought stress. However, there have been different outcomes of protein accumulation in plants under stress conditions, and the increased expression of these proteins contributes to plant stress management …”
Section: Discussionmentioning
confidence: 99%
“…It is well known that proline accumulates in plant tissue under unfavourable environmental conditions, especially salinity and drought [ 73 ]. Proline protects proteins, membranes, and cellular structures from damage by scavenging reactive oxygen species (ROS) in tissue [ 74 , 75 , 76 ]. Many previous works recorded an increase in proline content in some crops, such as tomatoes [ 4 ], broad bean [ 9 ], and green beans [ 29 ], under saline conditions.…”
Section: Discussionmentioning
confidence: 99%